Relationships between achievement goals and doping in cycling: Exploring the mediating role of athlete burnout - Filleul, V.; d`Arripe-Longueville, F.; Bimes, H.; Maillot, J.; Meinadier, E.; Isoard-Gautheur, S.; Corrion, K. (Journal of Sports Sciences, 2024)
Doping remains a pressing issue in competitive sport. This study investigated the relationships between achievement goals and doping by examining the mediating role of athlete burnout. French competitive cyclists (N = 251, Mage = 24.95, SD = 9.85) completed a survey measuring 2 × 2 achievement goals, burnout (i.e. physical exhaustion, reduced accomplishment, negative feelings towards sport, cognitive weariness), doping attitudes and likelihood. Structural equation modelling revealed that performance-approach goals were negatively related to each dimension of burnout and to doping likelihood with a total effect (ß = -.10; p < .05). A significant total effect (ß = .23; p < .05), as well as direct (ß = .17; p < .05) and indirect through the mediating role of cognitive weariness (ß = .06, 95% CI = [0.025, 0.601]) were observed between performance-avoidance goals and doping attitudes. The model explained 11.9% of the doping likelihood variance. Burnout may play a key role in understanding the relationships between achievement goals and doping. Considering both athletes` achievement goals and burnout thus appear as crucial for anti-doping efforts. Therefore, developing mental health interventions should be prioritized. Further experimental and longitudinal research is necessary to establish the temporal and causal effects of these relationships.